Orthogeriatrics - Falaschi, Paolo; Marsh, David R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book focuses on orthogeriatrics, a topic that has received little attention in the literature to date. As active members of the Fragility Fracture Network (FFN), the editors and most of the authors of this book have gathered all essential expertise on hip fracture management in a single volume. The 14 chapters provide a complete overview of how to approach fractures in elderly patients, starting with the epidemiology of hip fractures and subsequently addressing osteoporosis, surgery, anesthesia, medical management of frailty, and peri-operative complications. Attention is also given to rehabilitation and nursing, as well as to the psychological evaluation of the patient and the caregivers, thus emphasizing the importance of a multidisciplinary approach. Thanks to its clinical and practice-oriented nature, the book will especially be of interest to residents and young geriatricians, as well as orthopaedic surgeons, anesthesiologists and nurses dealing with elderly fracture patients in all parts of the world.
1 Introduction: why orthogeriatrics, worldwide distribution of orthogeriatric approach -- 2 Epidemiology of hip fracture and social costs.-3 Osteoporosis in the elderly patient -- 4 Frailty, sarcopenia and falls -- 5 Pre-operative management -- 6 Hip fracture: the choice of surgery -- 7 Orthogeriatric anaesthetics. 8 Post-operative management -- 9 The role of nursing -- 10 Rehabilitation -- 11 Multi-professional team: coordination and communication -- 12 How to implement a Fracture Liaison Service -- 13 Co-management of elective orthopaedic patients -- 14 Patient$1 (Bs and caregiver$1 (Bs psychological evaluation.s
Keywords: Medicine; Anesthesiology; Emergency medicine; Geriatrics; Nursing; Orthopedics; Medicine & Public Health; Geriatrics/Gerontology.; Orthopedics; Anesthesiology; Emergency medicine; Nursing